1998
DOI: 10.1007/pl00007020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pot Size and Timing of Plant Growth Regulator Treatments on Growth and Tuber Yield in Greenhouse-Grown Norland and Russet Burbank Potatoes

Abstract: The effects of pot size, timing of the application of paclobutrazol (PTZ) and gibberellic acid (GA 3 ), and the counteractive effect of these two compounds on growth and tuber yield of greenhouse-grown Norland and Russet Burbank potatoes were investigated. Plants were grown either in 1.5-liter pots (15 cm deep) or 3.0-liter pots (18 cm deep) and received a foliar application of either 1.5 mM PTZ or 9 × 10 −3 mM GA 3 at early or late stolon initiation. Some plants that had been foliar treated with 1.5 mM PTZ at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
3
14
0
1
Order By: Relevance
“…Paclobutrazol produced the maximum number of heavier and larger minituber than other PGRs (Table 2&4). The results of the present investigation are in agreement with the results of Kianmehr et al (2012) and Bandara et al (1998). Paclobutrazol is a triazole compound which inhibits extension growth in many plant species and blocks GA biosynthesis in plants (Davis et al, 1988).…”
Section: Discussionsupporting
confidence: 93%
“…Paclobutrazol produced the maximum number of heavier and larger minituber than other PGRs (Table 2&4). The results of the present investigation are in agreement with the results of Kianmehr et al (2012) and Bandara et al (1998). Paclobutrazol is a triazole compound which inhibits extension growth in many plant species and blocks GA biosynthesis in plants (Davis et al, 1988).…”
Section: Discussionsupporting
confidence: 93%
“…This result indicates that PBZ inhibiting effect was lower when the plants had a higher height at the moment of application, what could have been explained by an effect of dilution in the total mass of the plant or by some problem associated to the sites of action of the product (less activity and/or less sensitivity). The results found agree with those obtained by (Bandara et al 1998), who, evaluating the effect of time of PBZ application on vase-cultivated potatoes, observed that the effect of PBZ applied at the initial stages was higher than when applied at advanced culture stages.…”
Section: Resultssupporting
confidence: 82%
“…Thus, the use of growth regulators to reduce plant height may be a solution for plants cultivated under protected environment, as shown by some promising studies on banana plant growth regulation (El Otmani et al 1992, Jeyakumar et al 2003. Among the main growth regulators used in agriculture the most prominent is paclobutrazol (Khurshid et al 1997, Yim et al 1997, Bandara et al 1998, Rademacher 2000 EMANUEL MAIA et al Mouco and Albuquerque 2005). The main plant responses observed after paclobutrazol application are: smaller length of the new shoots, green color intensification, increased chlorophyll concentration and reduced foliar area (Khurshid et al 1997, Yim et al 1997, Carvalho et al 2005, Mouco and Albuquerque 2005.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 However, in the case of plants from TPS the effect of GA 3 varied with the method and time of application (Table 1). Thus single applications of GA 3 in the spring caused an increase in plant height irrespective of the stage of plant growth at the time of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…8 In contrast, a single application of exogenous GA 3 increased not only plant height but also tuberisation. 9 Since the levels of endogenous gibberellins vary during plant development, 10 it is likely that the effect of single applications will also vary with time.…”
Section: Introductionmentioning
confidence: 99%